Changes in the morphological and functional indicators of students in response to dosed physical activity - Andrii Yefremenko; Svitlana Рiatysotska; Krzystzof Prusik; Viktor Pavlenko; Vladyslav Rozhkov (Kharkiv State Academy of Physical Culture, 2022)
Purpose: to determine the features of changes in the morphological and functional indicators of students in response to a dosed physical load. Material & Methods: practically healthy students of 18±0.7 years of I-II courses of study (n=40) who did not regularly go in for sports in the past and present took part in the study. They were divided into test groups according to the following principle: group 1 (n=20) included students involved in playing sports (sports games and their elements); group 2 (n=20) included students involved in acyclic/cyclic types of physical culture and sports activities (types of athletics). Research methods: theoretical methods of pedagogical research; testing; hardware methods; mathematical and statistical. Results: the features of adaptation of the functional systems of the body of students to regular physical culture and sports classes by different types of motor activity of a predominant orientation were determined: gaming (sports games and their elements, mini-sports games); cyclic (types of athletics). It was revealed that as a result of regular classes according to training programs, both in terms of types of physical culture and sports, predominantly cyclic / acyclic (types of athletics), and game types (sports games and their elements), there is an improvement in the level of working capacity and endurance of students already in a two-month period. The reactions of the students' organism in response to the dosed physical activity of the Martin-Kushelevsky test at the end of the study allow us to assert an increase in the level of functioning and reserves of the cardiovascular system of the subjects as characteristics of the adaptation of the morphological and functional structures of the body to programmed regular physical exercises. However, when comparing the indicators of the studied groups, no significant differences were found. Consequently, the influence of predominantly different types of training loads is similar. This helps to deepen the understanding of the influence of academic physical education classes on the body of students. Consequently, the main determinant of increasing the level of adaptation to physical activity among students is the regularity of classes, while observing the pedagogical and specific sports principles of their construction. At the same time, the main goal of such classes should be to increase the level of general endurance as a characteristic of the level of physical health. Conclusions: morphological and functional changes in the body of students in the amount provided for by the program of physical education of higher education do not depend on the predominant nature of motor activity. As a result of the two-month training program, an improvement in the functional state of the students' body was revealed. However, this does not apply to the integral indicators of the functioning of the cardiovascular system. To improve the morphological and functional indicators of students, it is necessary to increase the time of regular physical education classes, regardless of the nature of motor activity.